A case of choledocholithiasis secondary to post cholecystectomy clip migration. (November 2017) - Shaker, Tamer; Hackett, Timothy
Abstract : Introduction: The commonly reported risks of a cholecystectomy include bile leak, bile duct injury, infection, bleeding, and retained gallstones. Approximately 1-2% of all patients who undergo cholecystectomy have stones left in the common bile duct (CBD) that require further intervention. The use of surgical clips to ligate the cystic duct has been routine since the advent of the laparoscopic cholecystectomy as the standard of care in the 1990s. One rare risk associated with the use of surgical clips is a migrated clip that can result in an obstructed CBD. Case description: The patient is a 72 year old male who presented with sudden onset, severe, right upper quadrant (RUQ) pain with associated nausea and vomiting after eating fried food. His past surgical history was significant for an uncomplicated laparoscopic cholecystectomy 7 years prior for acute cholecystitis. The patient had been having intermittent RUQ pain for 2 years prior to his presentation and had undergone an esophagogastroduodenoscopy that demonstrated mild gastritis. The patient had no other surgical or procedural history. On examination, the patient had mild tenderness to palpation in the RUQ. Of note, his labs were significant for a white blood cell count of 11000, aspartate aminotransferase of 760, alanine aminotransferase of 427 and total bilirubin of 3.0. A computed tomography scan demonstrated a hypodense lesion in the intrapancreatic common bile duct with the morphology of a surgical clip measuring 7mm. Magnetic resonance cholangio-pancreatography confirmed the CT findings. The decision was made to proceed with an endoscopic retrograde cholangio-pancreatography (ERCP) from which a clip inside a sludge ball was extracted. The patient tolerated the procedure well and underwent a routine post-procedure course. Results and Conclusions: Post cholecystectomy clip migration is a rare condition that can lead to choledocholithiasis and cholangitis. Predisposing factors that have been suggested include cholecystitis, postoperative complications and the use of an excessive amount of clips. It has been theorized that the mechanism for clip migration is secondary to inadvertent placement of clips in the biliary tree, clip slippage or subclinical bile duct injuries. The appropriate treatment strategy for choledocholithiasis secondary to post cholecystectomy clip migration is ERCP.